Three novel polymorphic microsatellite markers for the glaucoma locus GLC1B by datamining tetranucleotide repeats on chromosome 2p12-q12 - Murga-Zamalloa, C (2009)
Universidad de San Martin de Porres Funds, Lima, Per (Project number E20012003005), Consejo Nacional de Ciencia y Tecnolog a Per (CONCYTEC).